3+10y=-13-5y

Simple and best practice solution for 3+10y=-13-5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+10y=-13-5y equation:


Simplifying
3 + 10y = -13 + -5y

Solving
3 + 10y = -13 + -5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '5y' to each side of the equation.
3 + 10y + 5y = -13 + -5y + 5y

Combine like terms: 10y + 5y = 15y
3 + 15y = -13 + -5y + 5y

Combine like terms: -5y + 5y = 0
3 + 15y = -13 + 0
3 + 15y = -13

Add '-3' to each side of the equation.
3 + -3 + 15y = -13 + -3

Combine like terms: 3 + -3 = 0
0 + 15y = -13 + -3
15y = -13 + -3

Combine like terms: -13 + -3 = -16
15y = -16

Divide each side by '15'.
y = -1.066666667

Simplifying
y = -1.066666667

See similar equations:

| 3/2-x*7=7 | | 5+15b=-4b-5 | | -9-4x=-5-13x | | X-2k=x-6 | | 5-5x=13-4x | | 5x/b-9x/a=c | | -6z+10=-10z+8 | | v=1/3*6*50 | | R-183=91 | | 8+12a=-5a-13 | | Log(x+33)-log(x-2)=2 | | v=1/3*12*74 | | -12x+5=-5x-14 | | R-183= | | -7x-3=2-10x | | 37=p-13 | | 12-6z=-10z-7 | | 6x+4*2=5 | | 11+10x=-10x-4 | | 45v=315 | | 2-6b=-5+3b | | -5+4z=15+18z | | 14-6y=4+9y | | 14-8y=-14y-2 | | -3+9y=15+3y | | 3-11y=12y+4 | | 100=b+37 | | -15x-10=8x-4 | | x^100-0.01x=1 | | C-38=33 | | -9+9x=-4-14x | | -8+13z=8+14z |

Equations solver categories